Pengaruh Model Pembelajaran RME (Realistic Mathematics Education) pada Materi Bangun Datar Terhadap Kemampuan Numerasi Siswa Kelas VII SMPIT An-Nida’ Lubuklinggau - Aria Selfis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the effect of the Realistic Mathematics Education (RME) learning model on the numeracy skills of seventh-grade students at SMPIT An-Nida’ Lubuklinggau. The method used is an experimental approach with a quasi-experimental design. The population consisted of 54 seventh-grade students, divided into two groups: Class VII-2 as the experimental group and Class VII-3 as the control group. Data collection was conducted through observation, tests, and documentation. Data analysis techniques included prerequisite tests (normality test), Wilcoxon test, Mann-Whitney test, and N-Gain test. The results showed that the significance value (sig. 2-tailed) in the Independent Sample Wilcoxon and Mann-Whitney tests was 0.000, which is less than 0.05 (sig. 2-tailed ≤ 0.05). In conclusion, the Realistic Mathematics Education (RME) model positively influences the improvement of numeracy skills among seventh-grade students at SMPIT An-Nida’ Lubuklinggau. Keywords: Realistic Mathematics Education (RME), Numeracy Skills